Unusual case of tubercular peritonitis - Devi, L. Thulasi; R. S., Athul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
An interesting case of Pelvic Tubercular Peritonitis, post MTP and IUCD insertion presenting as Severe Sepsis. Managed aggressively with Fluid, supportive measures and complete course of ATT. Case is being reported as an unusual complication post MTP and incidental reports in literature of spread of Pelvic Peritonitis in preexisting Genital Tuberculosis by haematogenous spread.